2011
DOI: 10.1177/1059840511428615
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Overweight, Elevated Blood Pressure, and Acanthosis Nigricans Among Low-Income Middle School Students

Abstract: This longitudinal study examined the rates of overweight, elevated blood pressure, acanthosis nigricans, and their associated factors in third through fifth grade students over 4 years. Participants consisted of 279 students who participated in health screenings in 2002 and 2006. Hispanic students had significantly higher rates of overweight and acanthosis nigricans compared to White students. There was a sharp increase in elevated blood pressure from 2002 to 2006 among obese children. While 20% of the matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 23 publications
2
8
2
2
Order By: Relevance
“…Consistent with previous research on the increasing rate of students who are overweight with AN among middle school students (Kopping et al, 2011); researchers in the current study found that time effects were significant for children of the same gender and increased BMI. Children were more likely to have a positive AN marker in later years, compared to the data in the year 2005.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous research on the increasing rate of students who are overweight with AN among middle school students (Kopping et al, 2011); researchers in the current study found that time effects were significant for children of the same gender and increased BMI. Children were more likely to have a positive AN marker in later years, compared to the data in the year 2005.…”
Section: Discussionsupporting
confidence: 92%
“…In a longitudinal study of overweight, elevated BP, and AN among low-income middle school (third- through fifth-grade) students, a sharp increase was found in elevated BP from 2002 to 2006 among obese children. Also, Hispanic students had significantly higher rates of overweight and AN compared to non-Hispanic White students (Kopping et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The prevalence rates of childhood overweight and obesity in this study were similar to those reported in previous studies in the same region. 6,23,24 The rates found in this study were lower Table 2. groups and mean systolic (F 2,163 = 8.49; P < .01) and diastolic BP (F 2,163 = 5.80; P < .01).…”
Section: Discussioncontrasting
confidence: 59%
“…The link between obesity and EBP demonstrated in this investigation is consistent with that found in other investigations and supports the usefulness of BMI as a screening tool for increased risk of EBP. [20][21][22][23][24] A recent report from the American Academy of Pediatrics evinced that at least 1 CVD risk factor was present in nearly half of the nations' overweight children and in almost two-thirds of obese children. 9 Recommendations for regular early health screenings that include BP measurements have been made for children as young as preschool students; however, there are few mandatory, national, school-based health screenings that include BP measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation